2018
DOI: 10.1089/jmf.2017.4065
|View full text |Cite
|
Sign up to set email alerts
|

Red Pepper (Capsicum annuumL.) Seed Extract Decreased Hepatic Gluconeogenesis and Increased Muscle Glucose UptakeIn Vitro

Abstract: Red pepper seed, a by-product of red pepper, has been reported to have antioxidant and antiobesity activities. However, its role in diabetes has not yet been highly investigated. Glucose homeostasis is mainly maintained by insulin, which suppresses glucose production in the liver and enhances glucose uptake in peripheral tissues. In this study, we investigated the underlying mechanisms through which red pepper seed extract (RPSE) affects glucose production in AML12 hepatocytes and glucose uptake in C2C12 myotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The protein levels were eliminated by RPSE supplementation; PEPCK and G6Pase were reduced by 43% (p < 0.001) and 78% (p < 0.01), respectively, in ObD mice. Our previous in vitro study also demonstrated that RPSE reduced gluconeogenesis by inhibiting PEPCK and G6Pase proteins in AML12 murine hepatocytes [19]. These novel findings proved that RPSE supplementation transcriptionally downregulated the expression of gluconeogenic genes and proteins, including PEPCK and GP6Pase, in the liver of ObD mice.…”
Section: Rpse Downregulated Hepatic Gluconeogenic Genes and Proteins supporting
confidence: 52%
See 2 more Smart Citations
“…The protein levels were eliminated by RPSE supplementation; PEPCK and G6Pase were reduced by 43% (p < 0.001) and 78% (p < 0.01), respectively, in ObD mice. Our previous in vitro study also demonstrated that RPSE reduced gluconeogenesis by inhibiting PEPCK and G6Pase proteins in AML12 murine hepatocytes [19]. These novel findings proved that RPSE supplementation transcriptionally downregulated the expression of gluconeogenic genes and proteins, including PEPCK and GP6Pase, in the liver of ObD mice.…”
Section: Rpse Downregulated Hepatic Gluconeogenic Genes and Proteins supporting
confidence: 52%
“…As such, improved glucose uptake by RPSE supplementation in the ObD model was an innovative discovery. We previously demonstrated that 200 µg/mL of RPSE activated the translocation of GLUT4 to the plasma membrane followed by increasing glucose uptake in the C2C12 murine myotubes [ 19 ]. Similarly, there was a previous report that red pepper powder extracted using 70% ethanol improved insulin sensitivity and glycogen storage in liver and muscle tissues of ovariectomized rats fed a HFD [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory effects of natural compounds on gluconeogenic pathways in hepatocytes have been reported previously. The red pepper seed extract treatment decreased the mRNA levels of G6PC and PCK1 and suppressed glucose production in AML-12 cells [ 17 ]. However, whether the inhibition of HGP was caused by the regulation of the gluconeogenic pathway was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The HGP assay was conducted according to a previous study, with modifications [ 17 ]. AML-12 cells were seeded in a 6-well plate.…”
Section: Methodsmentioning
confidence: 99%